228k views
0 votes
Complete the statement 3^3•3^-2

2 Answers

6 votes

Answer:


3^3*3^-^2 = 3^3^+^(^-^2^) =3^1=3

Explanation:

This is as the exponent rule of multiplication states that the product of two powers with the same bases is the same base to the power of the sum of their exponents. As 3 + (-2) = 1, 3^3 times 3^-2 = 3^1 = 3.

User Jdstaerk
by
4.9k points
1 vote

Answer: Your answer to 3*3x3*2 is 243

Explanation:

This is because 3 to the 3rd power is 27. Then 3 to the 2nd power is 9. 27x9 s 243. Hope this helps.